Devolution of power and its intensity: issues and challenges in the case of sri lanka - Liyanahetti, D. (University of Jaffna, 2012)
Fiscal devolution is a major aspect of devolving power. Distribution of public expenditure, spending discretion and modalities for equalization of fiscal capacities were being debated and still being so. Fiscal decentralization has been adopted by both developing as well as developed countries under various circumstances all of which aims to accelerate economic growth effectuating a more balanced development especially at regional/provincial level. However, one of the most controversial debates has been on the fact of evaluating or measuring as to how far devolution has occurred. Unlike in Sri Lanka many other countries which have devolved power have invented few tools on this measuring aspect. Sri Lanka implemented fiscal decentralization through the 13th amendment to the Constitution during 1987/88 and with the establishment of the Provincial Council System. There is a strong argument that such devolution sought to facilitate ethnic cooperation by equally distributing resources from the center to the periphery. Nevertheless, seldom there have been comprehensive studies as to whether fiscal decentralization has resulted in the expected outcomes or rather a waste of physical resources in computable terms. The present study aims to mathematically measure to what extent fiscal decentralization has been implemented in Sri Lanka and identify the issues faced by the present sub-national government system. The results reveal that the degree of decentralization has been poor in many respects. In other words the de facto system of fiscal decentralization in Sri Lanka is still a resemblance of centralization than decentralization. As Sri Lanka is emanating from the debris of a 30 year conflict situation time has now arrived to evaluate the success or failure of the power devolution that was implemented more than two decades ago. Identifying such weakness and challenges would be essential to ensure a more balanced and even growth in the country as intended constitutionally.
Keywords: Fiscal decentralization; Regional growth; Measuring decentralization; Post-war economy